A randomized controlled trial comparing immersive virtual reality games versus nitrous oxide for pain reduction in common outpatient procedures in pediatric surgery - Cordula Scherer; Ladina A. Lanz; Thoralf R. Liebs; Nadine Kaiser; Mirjam Zindel; Steffen M. Berger (Trials)
Abstract Background Children often experience anxiety and pain during minor surgical procedures, prompting the search for effective pain management strategies beyond traditional pharmaceutical approaches. This study aims to evaluate the efficacy of virtual reality (VR) as a pain reduction method in pediatric outpatient surgical interventions compared to the standard use of nitrous oxide. The research questions explore pain reduction levels, patient preferences, enjoyment during VR use, and the time limit of the VR application. Methods The study employs a randomized controlled trial design, utilizing VR technology and nitrous oxide in separate groups in 100 children at the age from 6 to 15 undergoing minor surgical procedures. Outcomes are monitored directly after the intervention and two weeks following the procedure. The primary outcome measure is the pain level, assessed using visual face and visual analog scales. Secondary outcomes are the fun and/or fear experienced during the intervention, the willingness to undergo the same procedure again (if necessary), and whether there is a time limit with the VR application compared to nitrous oxide. The study also considers adverse events and safety measures. Discussion The study aims to address a significant research gap in pediatric pain management strategies, as it is the first randomized controlled trial designed to compare pain levels using VR versus a control group with nitrous oxide analgosedation in children undergoing minor surgical procedures. Preliminary evidence suggests VR may offer a viable alternative to traditional pain management methods, as VR technology could be an effective distraction and pain management tool for pediatric patients undergoing outpatient surgical procedures. Trial registration ClinicalTrials.gov NCT05510141. Registered on August 22, 2022. Virtual Reality Games in Pediatric Surgery—Full Text View—ClinicalTrials.gov. Trial sponsor The principal investigator, Cordula Scherer act as the Sponsor, Clinic for pediatric surgery, Inselspital, Bern University Hospital, CH 3010 Bern, Switzerland.